The Effect of Using Learning Management System Learning Media on Student Independence and Learning Outcomes - Purwitaning Rahayu, Dezy; Herpratiwi, Herpratiwi; Firdaus, Rangga (UNDIKMA, 2024)
In the learning process, good student learning motivation is created by the use of engaging learning media. When students become motivated, it will enhance their independence in learning, which in turn will lead to better learning outcomes. This research aims to conduct a literature review to explore the influence of using Learning Management Systems (LMS) on students' independence and learning outcomes. Additionally, the study seeks to identify alternative LMS platforms besides Moodle, Edmodo, and Google Classroom, which are widely used among educators in Indonesia. The research employs the Systematic Literature Review (SLR) method, which aims to identify, assess, and interpret all evidence from previous studies to find solutions to existing problems. The data collected from this research indicate that e-learning using LMS has been proven to enhance students' academic achievement and learning independence. Apart from Edmodo, Moodle, and Google Classroom, there are many other LMS platforms that educators can explore, such as Canvas LMS, which is equally attractive as other LMS platforms